Inside Cover: Synthetic Molecular Photoelectrochemistry: New Frontiers in Synthetic Applications, Mechanistic Insights and Scalability (Angew. Chem. Int. Ed. 12/2022). Issue 12 (22nd November 2021) - Wu, Shangze; Kaur, Jaspreet; Karl, Tobias A.; Tian, Xianhai; Barham, Joshua P.
Abstract : Molecular photoelectrochemistry, allowing access to a broader window of single electron transfer chemistry in a greener way, is a rapidly expanding toolbox for synthesis and selective functionalizations of complex molecules. In their Review (e202107811), Joshua P. Barham and co‐workers capture exciting synthetic opportunities, key mechanistic insights and evolving batch and flow reactor platforms allowing screening and scalability of reactions.